An empirical study of beliefs about work in Tonga : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Human Resource Management at Massey University - Lopeti, Mele 'Anitoni Lauteau Lucy (Massey University, 1997)
The aim of this research study was to identify the predominant beliefs that employed Tongan people hold about work, and to investigate the relationship between beliefs about work and selected demographic variables. The first step was to determine whether the instrument used to measure beliefs about work in the Tongan cultural context is a valid and appropriate measure. The sample consisted of 804 employed Tongans from Tongatapu, Vava'u, Ha'apai, 'Eua and Niuatoputapu islands. The sample was limited to Tongans employed mainly by government sector organisations that have an identifiable personnel function within paid employment in the formal economy of Tonga. Buchholz's Beliefs About Work Scale was used as the measure of employee attitude in the present study, using the same scales that have been developed in previous studies. This study attempted to replicate the five dimensions of the Beliefs About Work Scale and extend findings concerning beliefs about work in the Tongan context. It was concluded that the measurement of beliefs using the five dimensions from the Belief About Work Scale was not a valid and appropriate measure in Tonga. The results of the analysis revealed three factors of beliefs about work in Tonga. This suggests the need to sort out appropriate definitions and measurement in favour of research on indigenous samples, rather than simply applying results from countries of different cultural settings. Of the three factors of beliefs about work in Tonga, the highest mean scores were obtained on the humanistic belief system, then the work ethic, and the lowest mean scores were obtained on the leisure ethic. The analysis of variance of the factor scores revealed differences in beliefs exist in relation to gender, age and job level. Marital status and length of employment did not appear to be related to beliefs about work. These are discussed in this research study.
Keywords: Evaluation; Loyalty; Work ethic; Tonga; Employees; Commitment